2010
DOI: 10.1002/anie.201000520
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Singlet Dioxygen with Phosphine–Borane Derivatives: From Transient Phosphine Peroxides to Crystalline Peroxoboronates

Abstract: Singlet dioxygen is readily split by phosphine–boronates under mild conditions. The initially formed phosphine peroxides spontaneously rearrange by B→O migration. The resulting peroxoboronates have been structurally characterized, and their ability to undergo oxygen transfer reactions substantiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 60 publications
0
39
0
Order By: Relevance
“…It was found, however, that phosphine-borane 1-Ph2P-2-Bcat-C6H4 (7) was also generated in the reaction conditions (Scheme 6). This family of phosphinoboranes is well known and several derivatives were previously reported by Bourissou and coworkers [39][40]. The independent synthesis of 7 did show that this species does not react with CO2 nor with catecholborane (Scheme 7).…”
Section: Ambiphilic Molecules As Catalysts For the Reduction Of Carbomentioning
confidence: 86%
“…It was found, however, that phosphine-borane 1-Ph2P-2-Bcat-C6H4 (7) was also generated in the reaction conditions (Scheme 6). This family of phosphinoboranes is well known and several derivatives were previously reported by Bourissou and coworkers [39][40]. The independent synthesis of 7 did show that this species does not react with CO2 nor with catecholborane (Scheme 7).…”
Section: Ambiphilic Molecules As Catalysts For the Reduction Of Carbomentioning
confidence: 86%
“…[5] Ther eaction of triethylborane with triplet dioxygen is atypical example,which provides amethod of generating ethyl radicals. [6] Bourissou et al reported the addition/insertion reaction of singlet dioxygen to ap hosphane/ borane pair, [7] and there were several ways to form peroxy boron compounds that have been reported. [8] Agapie et al recently described the reduction of dioxygen by two molar equivalents of ferrocenes in the presence of the strong boron Lewis acid B(C 6 F 5 ) 3 to yield the bis(ferrocenium) bis(borane)peroxides 1a,b (Scheme 1).…”
mentioning
confidence: 99%
“…Selectedbondlengths []a nd angles [8]for 2a:P1 ÀC221.8179(11), C22À C23 1.5400(15), C23ÀO1 1.4068(13), C23ÀC24 1.5220(15), O1ÀB1 1.4909 (14), B1ÀC1 1.7023(16), C1ÀP1 1.7934(11);P1-C1-B11 15.77 (7),P 1-C22-C23 110.36 (7), C22-C23-O1107.78(9), C23-O1-B11 15.06(8). 2b:P1 ÀC22 1.8228 (12), C22ÀC231 .5479 (15),C 23ÀO1 1.4040 (14), C23ÀC241.5223(16), O1ÀB1 1.4838(15), B1ÀC1 1.6924(17), C1ÀP1 1.7872 (12);P1-C1-B1 115.77(8), P1-C22-C23 113.34(8), C22-C23-O1 110.02(9), C23-O1-B1 117.07(9).…”
Section: Resultsmentioning
confidence: 99%
“…The molecular structure of 3a is unambiguously established by single-crystal X-ray diffraction analysis (Figure 3, bottom) [24] and shows that the ring-opened 2-methyloxirane gives rise to Scheme3.Relative wB97X-D/6-31G(d,p) Gibbs free energies (in kcal mol À1 )for the conversion of 1 into 2a-c (only the methyl-substituted species a are shown;hydrogen atoms are omitted for clarity). (17),C22ÀC23 1.538(2),C 23ÀO1 1.403(2), C23ÀC24 1.532(2), O1ÀB1 1.519(2), C1ÀP1 1.7956 (19);P1-C22-C23 118.56 (12), C22-C23-O1 107.67 (15), C23-O1-B1119.77 (14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation